Priority to the private sector in EU-ACP cooperation. - LOGLI, Paolo (1994)
Describes the strategy being adopted by ACP countries to encourage private enterprise, mainly by offering incentives to better competitiveness and improving the rules and regulations. The strategy is founded on dialogue, reform and assistance and is underwritten with Lome funds.